Leadership Development Needs for School Principals - Nambinga, Salomo Mekondjo; Haufiku, Isidor (Papanda Publishier, 2024)
The main purpose of this study was to investigate leadership development needs of School Principals in selected schools in Omuthiya circuit in the Oshikoto Region, Namibia. The study used a mixed research approach, a convergent parallel research design. Data were collected using a questionnaire and structured interview guide. Twenty participants (20) were purposefully selected from 30 schools in Omuthiya Circuit in the Oshikoto Region. The study revealed that most school Principals in the study area do not have leadership skills and knowledge needed to set direction for schools; redesign their institutions, develop their staff and conduct instructional supervision. This lack of appropriate leadership skills and knowledge is impacting negatively on their execution of work. Another key finding was that the Regional Directorate has failed dismally to induct newly promoted Principals despite conducting fast tracked hand-over take-over mini-inductions. The presence of the CPD has not helped the Principals in acquiring the highly needed skills for the job, since very few workshops have been held due to financial limitations and lack of time. The study recommended that school Principals Omuthiya Circuit in the Oshikoto Region need to undergo leadership development training across all the four key practices, namely setting direction, instructional supervision, developing people and redesigning the organization, for them to be able to provide and demonstrate quality leadership skills which help improve their schools’ results.